148k views
2 votes
(1+cos2x)/(1-cos2x) = cot^2x

1 Answer

7 votes

We will turn the left side into the right side.


(1 + \cos 2x)/(1 - \cos2x) = \cot^2 x

Use the identity:


\cos 2x = \cos^2 x - \sin^2 x


(1 + \cos^2 x - \sin^2 x)/(1 - ( \cos^2 x - \sin^2 x)) = \cot^2 x


(1 - \sin^2 x + \cos^2 x )/(1 - \cos^2 x + \sin^2 x) = \cot^2 x

Now use the identity


\sin^2 x + \cos^2 x = 1 solved for sin^2 x and for cos^2 x.


(\cos^2 x + \cos^2 x )/(\sin^2 x + \sin^2 x) = \cot^2 x


(2\cos^2 x)/(2\sin^2 x) = \cot^2 x


(\cos^2 x)/(\sin^2 x) = \cot^2 x


\cot^2 x = \cot^2 x


User Mike Pierce
by
5.6k points